(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the production of virulence-associated enzymes, including protease, phospholipase, and lipase, in Candida albicans, Candida tropicalis and Candida parapsilosis isolated from patients with onychomycosis. Methods: A cross-sectional descriptive study was conducted on 90 Candida isolates obtained from patients diagnosed with Candida onychomycosis. Species identification was performed using carbohydrate assimilation tests with the API 20C system (bioMérieux–Vitek, France). Protease, phospholipase, and lipase activities were assessed using the spot inoculation method on specific enzyme-detecting media, following previously published protocols. Results: The overall proportions of Candida spp. exhibiting protease, lipase, and phospholipase activity were 82.2%, 77.8%, and 36.7%, respectively. Both C. albicans and C. tropicalis demonstrated very high levels of protease and lipase activity (100% and 96.7%, respectively), whereas C. parapsilosis predominantly showed absent or low enzymatic activity; this difference was statistically significant (p<0.001). All three species exhibited low phospholipase activity; however, C. albicans showed a significantly higher positivity rate compared with the other species (p<0.001). Most clinical forms of Candida onychomycosis were associated with high frequencies of protease and lipase activity, with no statistically significant differences among clinical presentations (p>0.05). In contrast, phospholipase activity varied significantly across different clinical manifestations (p<0.05). Conclusion: Candida spp. causing onychomycosis exhibit high rates of protease and lipase production, highlighting the important role of these enzymes in fungal pathogenicity. Although phospholipase is produced at a lower frequency, its activity is significantly associated with more invasive clinical forms of nail involvement.